Forest recollections : wandering monks in twentieth-century Thailand - Tiyavanich, Kamala, 1948- (University of Hawai'i Press, 1997)
"During the first half of this century the forests of Thailand were home to wandering ascetic monks. They were Buddhists, but their brand of Buddhism did not copy the practices described in ancient doctrinal texts. Their Buddhism found expression in living day-to-day in the forest and in contending with the mental and physical challenges of hunger, pain, fear, and desire. Combining interviews and biographies with an exhaustive knowledge of archival materials and a wide reading of ephemeral popular literature, Kamala Tiyavanich documents the monastic lives of three generations of forest-dwelling ascetics and challenges the stereotype of state-centric Thai Buddhism." "Although the tradition of wandering forest ascetics has disappeared, a victim of Thailand's relentless modernization and rampant deforestation, the lives of the monks presented here are a testament to the rich diversity of regional Buddhist traditions. The study of these monastic lineages and practices enriches our understanding of Buddhism in Thailand and elsewhere."--Jacket